PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION MELALUI PAY GRADE PADA KARYAWAN DI INDUSTRI KECIL SIDOARJO - Egalita Dian Yulianita Putri; Wahyu Eko Pujianto (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study aims to examine the Effect of Workload and Work Stress on Turnover intention through Pay grade in Sidoarjo small industry employees. The data collection technique uses saturated samples by distributing questionnaires with a sample of 99 respondents. The data analysis method used is descriptive quantitative analysis with a research design using partial least squares (PLS) using the SmartPLS Version 3.0 software program. The results obtained in this study stated that 4 of the 5 formulated hypotheses were accepted and 1 hypothesis was rejected. It is proven that one of the hypotheses has a t statistic value of 0.724 <1.96 with a P value of 0.353. this indicates that workload has a negative and insignificant effect on turnover intention through pay grade. While workload, work stress, pay grade have a positive and significant effect on turnover intention. Furthermore, in the results of the mediation test, the results of Workload -> Pay grade -> Turnover intention have a P Value of 0.734 which means it is not significant because the P Value > 0.05 and the T statistic value < 1.96 so it can be said that pay grade does not mediate workload on turnover intention. While Work Stress-> Pay grade-> Turnover intention has a P Value of 0.000 which indicates that this variable has a significant effect and has a statistical T value <1.96 so that it can be said that Pay grade mediates Job Stress Against Turnover intention.